(untitled) (Journal of Universal Science Research, 2024)
The article discusses the prospects for the restoration of economic cooperation in order to preserve historical and cultural ties between the countries of the Great Silk Road in Central Asia. It analyzes the implementation of large-scale reforms of tourist trips, for the population or tourists, including familiarization of historical sites between certain cities. The main role is assigned to the improvement of the economy and the scientific study of historical places and its traditions.